The neutrophil to lymphocyte ratio, platelet to lymphocyte ratio, and mean platelet volume in patients with chronic otitis media and cholesteatoma (Annals of Medical Research, 2021)
Aim: The neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and mean platelet volume (MPV) are widely used simple markers of subclinical inflammation. We explored whether these parameters were affected in patients with chronic otitis media (COM) with and without cholesteatoma.Material and Methods: We studied 295 COM patients operated upon in our hospital and 135 healthy subjects were devoid of inflammation (controls). The patients were divided into two groups depending on cholesteatoma status: COM with cholesteatoma (the COMch group) and COM without cholesteatoma (the COM group). The groups were compared in terms of their NLRs, PLRs, and MPVs. The NLR and PLR were calculated by dividing the numbers of neutrophils and platelets by that of lymphocytes.Results: Of the 295 patients, 149 and 146 had COMch and COM, respectively. No significant difference (P 0.05) was evident in any of NLR, PLR, or MPV between the study groups.Conclusion: None of LNR, PLR, or MPV differed significantly in COM patients with and without cholesteatoma. Although inflammation plays an important role in cholesteatoma pathogenesis, any effect thereof is local rather than systemic.Keywords: Chronic otitis media; cholesteatoma; neutrophil to lymphocyte ratio; platelet to lymphocyte ratio; mean platelet volume.